Implementation of Monitoring and Evaluation oImplementation of Monitoring and Evaluation of Elementary School Infrastructure Facilities at The Nabire Regency Education Office in 2023f Elementary School Infrastructure Facilities at The Nabire Regency Education Office in 2023 - Friskha Jenny Pally; Baharuddin Baharuddin; Agustinus Ba’ka (Jurnal Indonesia Sosial Teknologi, 2025)
Monitoring and evaluation are crucial to ensure that existing facilities and infrastructure operate optimally. This study aims to understand and analyze the Implementation of Monitoring and Evaluation of Elementary School Facilities and Infrastructure at the Nabire Regency Education Office in 2023 through periodic monitoring and evaluation. This study establishes the research object at the Nabire Regency Education Office. This type of research is qualitative. The results of this study conclude that Monitoring facilities and infrastructure at the Nabire Regency Education Office is an essential step in improving the quality of education. With a systematic approach involving various parties, the Education Office can identify needs, implement appropriate improvements, and ensure quality education for all students. This activity is expected to support sustainable education development in Nabire Regency. The Nabire Regency Education Office faces complex challenges in monitoring and evaluating elementary school facilities and infrastructure, including human resources, infrastructure, budget, data, and community participation. However, the Education Office's commitment to taking responsive steps is expected to increase the effectiveness of monitoring and evaluation and positively impact the quality of education. The results of this evaluation are essential to formulate an action plan to overcome shortcomings and improve infrastructure to support a better and sustainable education process in elementary schools.